Application of the thin-layer chromatography method for analysis of plant antioxidant activity - N. V. Kupaeva; E. R. Vasilevskaya; L. V. Fedulova; E. A. Kotenkova (Пищевые системы, 2021)
Plants are a rich source of effective non-toxic biologically active substances. Various physicochemical methods of analysis are used for evaluation of plant antioxidant activity. Composition of ethanol extracts of red, yellow and white onion husks, dried rosemary, basil, and chaga were studied by high performance thin layer chromatography (HPTLC) method. The antioxidant activity of the obtained fractions on a chromatographic plate was assessed by subsequent DPPH screening. The extracts red and yellow onion husk and rosemary demonstrated the highest antioxidant activity, variability of the qualitative composition and similarity of antioxidant profiles, while extract of white onion husks did not contain any antioxidant classes. Intensive spots with Rf of 0.13-0.97 were observed along the whole chromatogram track corresponding to red onion husks. It was also found that all tested extract, excepting white onion husk and chaga, contained spots with varying degrees of intensity in the Rf range of 0.96-0.98, which corresponded quercetin Rf value.